AUTHENTIC LEADERSHIP IN SCHOOL ORGANIZATIONS - Bento, Antonio Veloso; Ribeiro, Maria Isabel (European Scientific Journal, ESJ, 2013)
This research study, descriptive and exploratory in nature, had as objectives to know the perceptions of the teacher/students of a graduation course in Educational Sciences about their leaders, measured and evaluated through the Authentic Leadership Questionnaire (ALQ) and to verify if existed differences between the public and private school organizations in the four characteristics defined for the ALQ: a) self-conscious; b) transparency; c) moral/ethics; d) balanced processing. A non-probabilistic sample by convenience consisted of 86 participants from Brazil. The results of this research study show that the level of authenticity of the leader, in the four characteristics defined for the ALQ, in the perception of the subjects inquired, is above of the moderate level. Having in account the type of school organization (public or private), the differences found in the levels of the four characteristics defined for the ALQ were not statistically significant even though, the leaders of the private schools demonstrated to possess slightly higher values in the four analysed sub areas.